POLA KEMITRAAN ANTARA PETANI TEBU RAKYAT DENGAN PTPN VII UNIT USAHA BUNGAMAYANG DALAM USAHATANI TEBU: KASUS DI DESA KARANG REJO KECAMATAN SUNGKAI SELATAN, LAMPUNG UTARA - -, SRIATI; JUNAIDI, ASHARI; ASRI GUSNITA, LISA (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 8, No. 2 Juli 2008, 2012)
The purposes of this research are (1) to compare partnership pattern between farmers of TRK members and TRB members at Karang Rejo village with PTPN VII Unit Usaha Bungamayang, (2) to analyze the factors (Capital, land use, access to land, and experience) correlated to the farmer’s decision as the members of TRK in Karang Rejo Village, (3) to compare the income of TRK farmer’s and TRB farmer’s. The research was conducted on April until May 2006 by survey method, and data was collected by disproportionate random sampling. The result showed that there are any differences of activities on partnership pattern between the TRK farmers and TRB farmers with PTPN VII UU Bungamayang. That is about right and duty of farmer, right and duty of PTPN VII UU Bungamayang, credit, and distribution of produce. The capital, access to broad site and experience factor was having correlation with the farmer’s decision as the member of TRK. While size of land use was have no correlation with the farmer’s decision as the member of TRK. The average income at TRK farmers was Rp. 15.969.443,23 per hectare, while the income the TRB farmers was Rp. 13.591.636,84 per hectare. The differences of the average income was Rp 2.377.806,39 per hectare. Keywords: Partnership Patter, Cane Sugar, Farmers, Income.
Keywords: Partnership Patter, Cane Sugar, Farmers, Income. (Pola Kemitraan, Gula Tebu, Petani, Pendapatan)